2015
DOI: 10.1016/j.celrep.2014.12.012
|View full text |Cite
|
Sign up to set email alerts
|

HUWE1 Ubiquitylates and Degrades the RAC Activator TIAM1 Promoting Cell-Cell Adhesion Disassembly, Migration, and Invasion

Abstract: SummaryThe E3 ubiquitin ligase HUWE1, deregulated in carcinoma, has been implicated in tumor formation. Here, we uncover a role for HUWE1 in cell migration and invasion through degrading the RAC activator TIAM1, implying an additional function in malignant progression. In MDCKII cells in response to HGF, HUWE1 catalyzes TIAM1 ubiquitylation and degradation predominantly at cell-cell adhesions, facilitating junction disassembly, migration, and invasion. Depleting HUWE1 or mutating the TIAM1 ubiquitylation site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 32 publications
(43 reference statements)
0
49
0
1
Order By: Relevance
“…TIAM1 was detected predominantly in nuclei from all three cell lines (Figure 2A). Furthermore, depletion of TIAM1 using two different small interfering RNAs (siRNAs) reported previously (Vaughan et al., 2015, Whalley et al., 2015) dramatically reduced the nuclear signal in all three lines (Figure 2A), verifying the specificity of the staining. Specificity of the nuclear TIAM1 staining was also verified in two independent clones of SW480 cells with TIAM1 ablated using CRISPR (Figures S2A–S2C).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…TIAM1 was detected predominantly in nuclei from all three cell lines (Figure 2A). Furthermore, depletion of TIAM1 using two different small interfering RNAs (siRNAs) reported previously (Vaughan et al., 2015, Whalley et al., 2015) dramatically reduced the nuclear signal in all three lines (Figure 2A), verifying the specificity of the staining. Specificity of the nuclear TIAM1 staining was also verified in two independent clones of SW480 cells with TIAM1 ablated using CRISPR (Figures S2A–S2C).…”
Section: Resultsmentioning
confidence: 96%
“…Previous work has shown that oncogenic RAS expression suppresses TIAM1 transcription (Zondag et al., 2000). Furthermore, we and others have identified E3 ubiquitin ligases targeting TIAM1 for degradation (Genau et al., 2015, Magliozzi et al., 2014, Vaughan et al., 2015, Zhu et al., 2014), which may be deregulated in intestinal carcinoma. Potentially, factors resulting in exclusion of TIAM1 from the nucleus might also result in downregulation of this critical suppressor function of TIAM1, and we are currently investigating the mechanisms regulating TIAM1 nuclear import and export.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in response to HGF stimulation, E3 ubiquitin protein ligase HUWE1 (HECT, UBA and WWE domain containing 1) catalyses the ubiquitylation and degradation of TIAM1 at sites of cell-cell adhesion 85 . The decrease in active TIAM1 results in the disassembly of the junctions and promotes an invasive phenotype in MDCKII epithelial cells 85 . The RhoA GEF ephexin 5 is ubiquitylated in response to ephrin type-B receptor 2 (EphB) stimulation in neuronal cells 86 .…”
Section: Nature Reviews | Molecular Cell Biologymentioning
confidence: 99%
“…Tiam1-Rac can enhance lamellipodia and invadopodia formation in breast cancer at a low cell density [130] but it can also promote E-cadherin-mediated adhesion in MDCKII cells [131, 132]. In accordance with the role of Tiam1 in maintaining the cell junction structure, Vaughan et al have shown that in response to HGF, Tiam1 can be ubiquitinated at Lys-595 by HUWE1, resulting in Tiam1 degradation and disassembly of cell junctions, increasing cell migration and invasion in lung carcinoma cells [126]. HGF-induced Rac1-mediated cell migration is regulated by another HECT E3 ligase, HECT domain and Ankyrin repeat containing E3 ubiquitin-protein ligase 1 (HACE1), which degrades Rac itself [133].…”
Section: Substrates Of Huwe1mentioning
confidence: 99%